Life expectancy of individuals on combination antiretroviral therapy in high-income countries: a collaborative analysis of 14 cohort studies. (Lancet, 2008)
Combination antiretroviral therapy has led to significant increases in survival and quality of life, but at a population-level the effect on life expectancy is not well understood. Our objective was to compare changes in mortality and life expectancy among HIV-positive individuals on combination antiretroviral therapy.
Keywords: Adolescent; Adult; Antiretroviral Therapy, Highly Active; Cohort Studies; Developed Countries; Female; HIV Infections; Humans; Life Expectancy; Life Tables; Male; Middle Aged; Multicenter Studies as Topic; Sex Factors